Goal programming to evaluate the profile of the most profitable insurers: an application to the Spanish insurance industry. (9th March 2020) - González‐Fernández, Ana Isabel; Rubio‐Misas, María; Ruiz, Francisco
Abstract: This paper applies a multiobjective goal programming (GP) model to define the profile of the most profitable insurers by focusing on 14 firm‐decision variables and considering different scenarios resulting from the exogenous change in interest rate and GDP per capita growth variables. We consider a detailed database of Spanish non‐life insurers over the period 2003–2012 taking into account two dimensions of insurers' results: underwriting results and investment results. A prior econometric analysis is used to find out relevant relations among the variables. Next, a GP model is formulated on the basis of the relationships obtained. The model is tested in a robust environment, allowing changes in the coefficients of the objective functions, and for several scenarios regarding crisis/noncrisis situations and changes in interest rates. We find that having the stock organizational form, being an unaffiliated single company and maintaining low levels of investment risk, leverage, and regulatory solvency are recommended for result optimization. Growth and reinsurance utilization are not advisable for optimizing the results, whereas size should be positively emphasized even more in instability periods and when interest rates increase. The results also show that the optimal level of the diversification/specialization strategy depends on economic conditions. More specialization is advisable as negative changes in interest rates increase. However, we find that the optimal values of the diversification variable are higher for the crisis scenarios compared to the corresponding noncrisis scenarios, suggesting that diversification creates value in crisis. Further sensitivity analyses show the soundness of the conclusions obtained.